A comparative analysis of European and British cosmetic products legislation - Kramarczuk, Patrycja; Gałęcki, Krystian (Wydawnictwo Politechniki Łódzkiej, 2023)
Due to the withdrawal of the United Kingdom of Great Britain and Northern Ireland from the European Union (EU), cosmetic products made available in this country are no longer subject to European legislation, but to British cosmetics law. The exit process (Brexit) was a rather chaotic event with not fully known consequences. The legal changes brought about by Brexit are difficult to understand for many cosmetic companies. Therefore, the aim of this work was to compare and demonstrate the legal differences between European and British cosmetic law, resulting from the withdrawal of the United Kingdom from the EU. The main differences concern the issues related to the responsible person, notification, documentation and labelling of the cosmetic product.
Keywords: cosmetic law; Brexit; regulation 1223/2009; prawo kosmetyczne; rozporządzenie 1223/2009